2016
DOI: 10.1055/s-0036-1596582
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization and immunomodulating effects of polysaccharides isolated from Dendrobium officinale

Abstract: A crude polysaccharide fraction (cDOP) has been determined to be the characteristic marker of Dendrobium officinale, an expensive tea material in Asia, but its chemistry and bioactivity have not been studied. In work reported here, cDOP was de-starched (DOP, 90% yield), and separated into two polysaccharides, DOP-1 and DOP-2, which were characterized by monosaccharide composition and methylation analyses, and spectral analyses (FT-IR and 1 H and 13 C NMR). Both are composed of mannose and glucose, at similar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…HPLC and LC-MS analyses indicated that DOP was mainly composed of D-glucose (830.98 mg/g) and D-mannose (59.19 mg/kg), in accordance with a previous study (Wei et al, 2016). As an essential glyconutrient for human health, mannose is a popular nutritional and health-beneficial food supplement (Hu et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…HPLC and LC-MS analyses indicated that DOP was mainly composed of D-glucose (830.98 mg/g) and D-mannose (59.19 mg/kg), in accordance with a previous study (Wei et al, 2016). As an essential glyconutrient for human health, mannose is a popular nutritional and health-beneficial food supplement (Hu et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…D. officinale has been widely used in porridge, soup and dishes as a highquality health food in diets and was approved by the China Food and Drug Administration (CFDA) (Meng et al, 2013;Wei et al, 2016). Phytochemical analyses showed that D. officinale was mainly composed of polysaccharides, with some low molecular weight compounds such as bibenzyls, phenanthrenes and flavanones (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4a, most of the absorption bands could be assigned in accordance with the previous literature (Xing et al, 2015;Wei et al, 2016). 4a, most of the absorption bands could be assigned in accordance with the previous literature (Xing et al, 2015;Wei et al, 2016).…”
Section: Infrared Spectroscopic Analysissupporting
confidence: 86%
“…The phenol-sulphuric acid assay, with glucose as a standard, was used to determine the total sugar content, and the modified carbazole and sulphuric acid method, with D-glucuronic acid as the standard, was used to determine the uronic acid content (Masuko et al, 2005;Westwood et al, 2011). The O-acetyl content was determined by phenolphthalein endpoint titration (Wei et al, 2016). The O-acetyl content was determined by phenolphthalein endpoint titration (Wei et al, 2016).…”
Section: Molecular Weight Determinationmentioning
confidence: 99%
See 1 more Smart Citation